Hey presto! (Scholastic, 2009)
Daniel's grandmother is a magician however his teacher Mr Grimshaw doesn't believe in such things. On Grandparent's Day, Gran decides she'll do her own rendition of 'Danny boy', but when someone else sings that song, and then Mr Grimshaw is a little insulting about magic tricks, to Daniel's delight, Gran decides to make Mr Grimshaw disappear. Suggested level: junior, primary